2010
DOI: 10.1007/s10661-010-1603-4
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and selenium levels in lemon sharks (Negaprion brevirostris) in relation to a harmful red tide event

Abstract: Tissue levels of mercury (Hg; total, organic) and selenium (Se) were assessed in juvenile lemon sharks (Negaprion brevirostris) from Florida nearshore waters collected during a harmful algal bloom (HAB, brevetoxin) event and compared with sharks not exposed to HABs. In all sharks studied, total Hg levels in the muscle were generally present in a molar excess over Se (which may protect against Hg toxicity) and mean muscle Hg levels (0.34 microg/g) exceed safe human consumption guidelines. While there was genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 49 publications
(70 reference statements)
3
7
0
Order By: Relevance
“…In addition, MeHg was measured in a subset of sharks with concentrations ranging from 0.05 to 1.95 ng/mg and a mean concentration of 0.42 ± 0.11 ng/mg (Table 4). THg and MeHg concentration in shark samples tested were highly correlated (Spearman correlations r = 0.94, p < 0.0001; n = 18) in our shark cohort as expected [33,34,35]. …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, MeHg was measured in a subset of sharks with concentrations ranging from 0.05 to 1.95 ng/mg and a mean concentration of 0.42 ± 0.11 ng/mg (Table 4). THg and MeHg concentration in shark samples tested were highly correlated (Spearman correlations r = 0.94, p < 0.0001; n = 18) in our shark cohort as expected [33,34,35]. …”
Section: Resultssupporting
confidence: 85%
“…Shark samples were analyzed for BMAA using high performance liquid chromatography with fluorescence detection (HPLC-FD) and Hg concentrations were quantified by cold vapor atomic fluorescence spectrometry (CVAFS). Since the total Hg (THg) that is measured in shark muscle and fin is mostly in the form of MeHg+, measures of total Hg are generally equivalent to MeHg+ [33,34,35] Here, THg concentrations in fin and muscle samples were measured and compared to MeHg+ for confirmation of levels in select samples. Our results demonstrated that all 10 shark species tested positive for both BMAA and Hg.…”
Section: Introductionmentioning
confidence: 99%
“…5b). Hg is likely sequestered by metallothioneins and other protective proteins, such as selenium proteins (Nam et al 2011). From in vivo assay studies, proposed Hg and Se toxicokinetics when fishes are exposed to MeHg and Se, accumulation is much lower in all organs than when fishes are exposed solely to MeHg, this may result from (Yang et al 2008;Branco et al 2012): (i) excess Se induce an increased production of selenoprotein, with the selenocysteine in this protein acting as a trap for MeHg keeping it in circulation and preventing its entry to the different organs; (ii) selenium preventing MeHg interactions with proteins by competing for the binding sites (SeH and SH groups); and (iii) Se binding MeHg during coexposure enhancing its excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Large size individuals of P. glauca had greater mercury and lead concentrations than small individuals. This is a well-documented process [12,13,20,[25][26][27][28][29][30][31][32][33][34] known as bioaccumulation [25,28,35]. The bioaccumulation process can take different pathways, one of which is through the diet (biomagnification).…”
Section: Discussionmentioning
confidence: 99%